Pentecotism and migration - (:unkn) unknown (My University, 2008)
The City of Zion is one of the numerous pentecostal churches blossoming in France in the immigration fields. Initiated in decembre 2000 by a Congolese prophet, its members are now about sicty coming from West Indies and french-speaking African countries. From the first of the prophet activities to the crisis that put an, end to his legitimacy, this study has been ficused on the formation of the young leaders to whom has been left the administration of the assembly. This gives us indications on the establishment modes of a world pentecotism that influences greatly, by its African expression, the new lecture of the migration path.
Keywords: African Research